Aberrant proliferation and differentiation of glycogen storage disease type Ib mesenchymal stem cells. Issue 2 (3rd January 2018) - Sim, Sang Wan; Park, Tae Sub; Kim, Sung‐Jo; Park, Byung‐Chul; Weinstein, David A.; Lee, Young Mok; Jun, Hyun Sik
Abstract : Glycogen storage disease type Ib (GSD‐Ib) is caused by mutations of the glucose‐6‐phosphate transporter (G6PT) and characterized by disrupted glucose homeostasis, neutropenia, and neutrophil dysfunction. To investigate the role of G6PT in human adipose‐derived mesenchymal stem cells (hMSCs), the G6PT gene was mutated by CRISPR/Cas9 technology and single cell‐derived G6PT −/− hMSCs were established. G6PT −/− hMSCs have significantly increased cell proliferation but impaired adipogenesis and osteogenesis. These phenotypes are associated with two mechanisms: i) metabolic reprogramming in G6PT −/− hMSCs causing a metabolic shift toward glycolysis rather than oxidative phosphorylation and ii) increased cyclooxygenase‐2‐derived prostaglandin E2 secretion in G6PT −/− hMSCs. This study demonstrates that G6PT is essential for proliferation and differentiation of MSCs, providing important insights into the GSD‐Ib phenotypes. Abstract :